ZIKIR DAN KETENANGAN JIWA DALAM PERSPEKTIF PSIKOLOGIS-EDUKATIF - Hendra Julianto; Syamsurizal Yazid (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the concept of dhikr and inner peace, as well as to analyze the relationship between the two from a psychological-educational perspective. Field findings indicate that individuals who consistently practice dhikr exhibit greater emotional stability compared to the theoretical ideal, which suggests that such stability should require a longer and more complex process, thereby revealing a gap worth further investigation. This study employs a qualitative approach using a field research design, through participatory observation, in-depth interviews, and documentation, analyzed using an interactive analysis model and strengthened through source and method triangulation. The results show that dhikr functions as a psychological-educational habituation process that gradually shapes emotional regulation and reflective thinking patterns, rather than occurring instantly. The relationship between the intensity of dhikr and inner peace is reciprocal, where the quality of mindful engagement in dhikr also determines its effectiveness in fostering mental stability. These findings contribute to the achievement of the SDGs, particularly in the area of mental health and psychological well-being, while offering an integrative model between spiritual values and educational processes as an alternative approach to sustainably strengthening mental health.